Sport performance profile in men`s European handball: discriminant analysis between winners and losers - Skarbalius, A.; Pukenas, K. (World Congress of Performance Analysis of Sport IX, 2012)
Europeans have won olympic and world gold medals since modern indoor men` s handball became an international sport (1938) and an olympic sport (1972). The main method of objectifying the process in sports games is the use of notational analysis (O`Donoghue, 2005). The aim of this study was to illustrate discriminate indicators of sport performance between winners and losers in European men`s modern handball match activities. The data sets gathered from the publically available EHF website (http://eurohandball.com./activitiesnew/analysis) cover the five European Men`s Handball Championships (EMHC) held in 2002-2010. Each match was classified for each team as successful (won match and draw - for both teams) and non-successful. A discriminant analysis was employed to identify a subset of game-related statistics of 28 variables that discriminated between winning and losing teams in each of the five EMHC. The indicators were compared across EMHC`2002-2010, using a general linear model analysis of variance (ANOVA), with Tukey Post Hoc test, the ANOVA was evaluated as significant when there was a < 5% chance of making a type I error. Between 28 variables of sport performance 15 key indicators only with significant discriminant between winners and losers at least in one EMHC were considered. Winners were better (P < 0.05) than losers in 6 indicators throughout EMHC`2002-2010. Winners scored more goals (P < 0.01), were better in efficiency of total attacks (P < 0.001) and positional attacks (P < 0.01), performed more efficiently in shooting total (P < 0.001) and shooting from long distance (P < 0.01), and goalkeepers saved more throws (P < 0.05). Findings indicate that winning and losing teams played in the same pattern. The phenomenon is that teams scored more goals in the second half than in the first. Six indicators - goals scored, efficiency of total attacks and positional attacks, efficiency of total shots, shots efficiency from long distance, and shots saved by goalkeepers - are the key indicators of discriminant winners at the EMHC`2002-2010. Performance indicators such as efficiency of individual attacks, shots from wings and 7 m penalties, and efficiency in minority might be considered as the key indicators of temporal pattern at the EMHC`2002-2010. The normative profile of winners identified can help coaches and players to create performance profiles according to team quality (O`Donoghue, 2005; Sampaio et al., 2010). Therefore, handball coaches will benefit from awareness of these results, particularly when designing game strategies and making tactical decisions.